UJI DAYA ANALGETIK DAN ANTIINFLAMASI EKSTRAK ETANOLIK DAUN SINGKONG (Manihot utilissima Pohl.) PADA MENCIT GALUR SWISS - Paulina Maya Octasari; Daniar Kusuma Wardani; Elisabeth Lionida Sari (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2022)
Background: Flavonoids are compounds that can function as analgesics and anti-inflammatory. Cassava leaves are known to contain flavonoids with the main content of rutin. The routine flavonoid content in the ethanolic extract of cassava leaves is 4.987% so that it has the potential to be developed as traditional medicine. Objective: This study aimed to determine the analgesic and anti-inflammatory properties of cassava leaf ethanolic extract (EEDS) and the effect of varying doses of EEDS on analgesic and anti-inflammatory properties. Methods: This study was a completely randomized experimental study with a unidirectional pattern in mice aged 2-3 months and weighing 20-30 grams. Analgesic testing method used the stretching method with 1% acetic acid as the induction, while the anti-inflammatory test used the edema thickness measurement method with 1% carrageenin induction. The results of the percentage of protection, the change in the percentage of protection, and the percentage of anti-inflammatory power were statistically analyzed. Results: The results showed that EEDS was green-black in color, bitter in taste, 7% drying loss, 12.31% w/w yield and positive for flavonoids. EEDS has analgesic power at a dose of 70; 140; and 280 (mg/kgBB) with a percentage of protection of 26.59%; 24.45%; and 21.96%; change in percentage of protection by 65.75%; 68.51%; and 71.72%. EEDS at a dose of 35; 70; and 140 (mg/kgBW) has a percentage of anti-inflammatory power of 44.93%; 37.34%; and 30.75%. Conclusion: The higher the dose of EEDS, the higher the analgesic power but the lower the anti-inflammatory power